Influence of Mechanical Stimuli on Schwann Cell Biology - Belin, Sophie; Zuloaga, Kristen L.; Poitelon, Yannick (Frontiers in Cellular Neuroscience, 2017)
Schwann cells are the glial cells of the peripheral nervous system. They insulate axons by forming a specialized extension of plasma membrane called the myelin sheath. The formation of myelin is essential for the rapid saltatory propagation of action potentials and to maintain the integrity of axons. Although both axonal and extracellular matrix signals are necessary for myelination to occur, the cellular and molecular mechanisms regulating myelination continue to be elucidated. Schwann cells in peripheral nerves are physiologically exposed to mechanical stresses (i.e.: tensile, compressive and shear strains), occurring during development, adulthood and injuries. In addition, this is a growing body of evidences that Schwann cells are sensitive to the stiffness of their environment. In this review, we detail the mechanical constraints of Schwann cells and peripheral nerves. We explore the regulation of Schwann cell signalling pathways in response to mechanical stimulation. Finally, we provide a comprehensive overview of the experimental studies addressing the mechanobiology of Schwann cells. Understanding which mechanical properties can interfere with the cellular and molecular biology of Schwann cell during development, myelination and following injuries opens new insights in the regulation of peripheral nervous system development and treatment approaches in peripheral neuropathies.